Systematic risk during 2008–2009 recession in emerging markets: some evidence from V3 and Baltic economies - Pošta, Vít; Pikhart, Zdeněk (Journal of Business Economics and Management, 2013)
Abrupt and profound swings in economic activity can result in changes in systematic component of risk premia of capital market assets. This can translate into adjustments in risk perception by the market agents, which may lead to significant changes in real investment development. We examine the issue of time-varying systematic risk on a micro level using the capital asset pricing model in an intertemporal setting. We formulate the hypothesis within a bivariate GARCH-in-mean model, which enables us to estimate the time-varying variances and covariances of the respective assets and market returns and thus the time-varying sensitivity to systematic risk. The results of the paper show that the reaction of assets’ sensitivity to systematic risk varies across the sample and the changes were rather temporary. Based on the results, the downturn in economic activity witnessed in 2008 – 2009 should not be a drag on real investment.